Sistemática e filogenia de Mahanarva (Ipiranga) com a descrição de duas novas espécies - Meneghetti, Jéssica (2020)
The spittlebug family Cercopidae are characterized by their bright colour patterns, head narrow than pronotum and the amount of protective froth excreta produced by their nymphs to complete their development. The genus of this study includes Mahanarva and Ferorhinella. Mahanarva includes 46 species distributed in the neotropical region and Ferorhinella includes two described species. The aim of this study was to provide a taxonomic revision of Mahanarva (Ipiranga), redescribe its species, describe a new species and propose a phylogenetic hypothesis within subgenus. Moreover, describe a new species of Ferorhinella and provide a diagnosis, illustrations and taxonomic notes for the other species within genus. Specimens examined are deposited in the following institutions: Museu de Ciências e Tecnologia da Pontifícia Universidade Católica do Rio Grande do Sul, Porto Alegre (MCTP), Departamento de Zoologia da Universidade Federal do Paraná, Curitiba (DZUP), Coleção Entomológica Prof. José Alfredo Pinheiro Dutra, Instituto de Biologia, Universidade Federal do Rio de Janeiro (DZRJ) and Coleção da Universidade Federal de Santa Maria (UFSM). Based on morphological data, a phylogenetic matrix was made with 18 taxa and 51 characters on software Winclada v1.00.08 and the most parsimonious tree was obtained on software TNT v1.5. For branch support we used Bremer support and bootstrap. Mahanarva (Ipiranga) was elevate to genus Ipiranga and recovered as monophyletic group and sister group of Mahanarva (Mahanarva) + Kanaima. The species of Ferorhinella, found in high altitudes along the coast of southeastern and southern Brazil, shared an unusual feature: F. balatra e F. itatiaiensis sp. nov. females are smaller than the males, and its body shape is rounded. Despite of F. brevis female were not yet sampled and described, it is assumed that this pattern is a trait shared by all species of this genus.